Color Gradients and Half-mass Radii of Galaxies Out to z = 2 in the CANDELS/3D-HST Fields: Further Evidence for Important Differences in the Evolution of Mass-weighted and Light-weighted Sizes - Tim B. Miller; Pieter van Dokkum; Lamiya Mowla (The Astrophysical Journal, 2023)
Recent studies have indicated that the ratio between half-mass and half-light radii, r _mass / r _light , varies significantly as a function of stellar mass and redshift, complicating the interpretation of the ubiquitous r _light − M _* relation. To investigate, in this study we construct the light and color profiles of ∼3000 galaxies at 1 < z < 2 with $logM_{* }/M_{\odot }\gt 10.25$ using imcascade , a Bayesian implementation of the Multi-Gaussian Expansion (MGE) technique. imcascade flexibly represents galaxy profiles using a series of Gaussians, free of any a priori parameterization. We find that both star-forming and quiescent galaxies have, on average, negative color gradients. For star-forming galaxies, we find steeper gradients that evolve with redshift and correlate with dust content. Using the color gradients as a proxy for gradients in the M / L ratio, we measure half-mass radii for our sample of galaxies. There is significant scatter in individual r _mass / r _light ratios, which is correlated with variation in the color gradients. We find that the median r _mass / r _light ratio evolves from 0.75 at z = 2 to 0.5 at z = 1, consistent with previous results. We characterize the r _mass − M _* relation, and we find that it has a shallower slope and shows less redshift evolution than the r _light − M _* relation. This applies both to star-forming and quiescent galaxies. We discuss some of the implications of using r _mass instead of r _light , including an investigation of the size−inclination bias and a comparison to numerical simulations.